Hubungan Perilaku Swamedikasi Antibiotik dengan Kejadian Resistensi pada Keluarga Petani di RSD dr. Soebandi Jember - Namira Kirana Djatmiko (Fakultas Kedokteran, 2024)
Self-medication in Indonesia is often irrational, especially in the use of antibiotics without a doctor's prescription, which contributes to antibiotic resistance. WHO estimates that antibiotic resistance could cause 10 million deaths annually by 2050 if there are no effective interventions. Farmers as the largest group of the Indonesian workforce often use antibiotics in self-medication for families, including children and the elderly, which can increase the risk of resistance. This study aims to determine the relationship between antibiotic selfmedication practice and the incidence of resistance in farmer’s families in RSD dr. Soebandi Jember. This study was an analytic observational study with a crosssectional approach conducted on 43 respondents in the urology clinic of RSD dr. Soebandi Jember. Antibiotic self-medication practice was measured using a questionnaire and bacterial culture sensitivity test results using medical record data. Chi-Square test was used to assess the relationship between research variables. Out of 43 respondents, the majority were in the age group of 40-59 years (n=24, 55.8%). Antibiotic self-medication practice was mostly in the good category (n=25, 58.1%). The highest bacterial culture sensitivity test results were resistant (n=39, 90.7%) with the most bacteria being Escherichia coli (n=11, 25.6%). Sulfonamides, fluoroquinolones, and cephalosporins were mostly resistant based on group. The result for the relationship between antibiotic self-medication practice and the incidence of resistance overall or by class was not significant (p>0.05). In conclusion, There is no relationship between antibiotic self-medication practice and the incidence of resistance in the family of farmers in RSD dr. Soebandi Jember.
Keywords: antibiotics self-medication; antibiotics resistance; bacterial culture sensitivity; farmer’s family